2013
DOI: 10.1167/iovs.12-9513
|View full text |Cite
|
Sign up to set email alerts
|

Development of Latanoprost-Loaded Biodegradable Nanosheet as a New Drug Delivery System for Glaucoma

Abstract: Citation: Kashiwagi K, Ito K, Haniuda H, Ohtsubo S, Takeoka S. Development of latanoprost-loaded biodegradable nanosheet as a new drug delivery system for glaucoma. Invest Ophthalmol Vis Sci. 2013;54:5629-5637. DOI:10.1167/iovs.12-9513 PURPOSE. We investigated the IOP reduction and safety of latanoprost-loaded biodegradable nanosheet (LBNS) as a new antiglaucoma drug delivery system (DDS).METHODS. We fabricated a 40 nm thick multilayered biodegradable nanosheet that is composed of chitosan and sodium algina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…We found that the percentage occurrence of postoperative ocular hypertension was high (22.64%), which is in line with the findings of other studies. 6 , 11 …”
Section: Discussionmentioning
confidence: 99%
“…We found that the percentage occurrence of postoperative ocular hypertension was high (22.64%), which is in line with the findings of other studies. 6 , 11 …”
Section: Discussionmentioning
confidence: 99%
“…28 The maximum force (peak force) is controlled at each pixel to obtain force−distance curves which are then used as feedback signal. Figure 1 shows an example of the PF-QNM force−distance curve corresponding to the sample (Alg2.5/Chi) 10 . The Z-axis reflects the distance ramped by the piezo-scanner in the vertical direction.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Several formulations of latanoprost, including biodegradable nanosheets with sustained delivery up to 1 month, have been reported. [49][50][51] Recently, a subconjunctival injection of latanoprost-loaded egg phosphatidylcholine liposomes showed sustained IOP reduction for 120 days in a primate model of glaucoma. 52 A pilot study of this approach involving 6 human subjects has recently been conducted in Singapore.…”
Section: Discussionmentioning
confidence: 99%